Serial Sampling of Serum Protein Biomarkers for Monitoring Human Traumatic Brain Injury Dynamics: A Systematic Review - Thelin, Eric Peter; Zeiler, Frederick Adam; Ercole, Ari; Mondello, Stefania; Büki, András; Bellander, Bo-Michael; Helmy, Adel; Menon, David K.; Nelson, David W. (Frontiers in Neurology, 2017)
Background: The proteins S100B, neuron-specific enolase (NSE), glial fibrillary acidic protein (GFAP), ubiquitin carboxy-terminal hydrolase L1 (UCH-L1) and neurofilament light (NF-L) have been serially sampled in serum of patients suffering from traumatic brain injury (TBI) in order to assess injury severity and tissue fate. We review the current literature of serum level dynamics of these proteins following TBI and used the term “effective half-life” (t½) in order to describe the “fall” rate in serum Material and methods: Through searches on EMBASE, Medline and Scopus, we looked for articles where these proteins had been serially sampled in serum in human TBI. We excluded animal studies, studies with only one presented sample and studies without neuroradiological examinations. Results: Following screening (10,389 papers), n=122 papers were included. The proteins S100B (n=66) and NSE (n=27) were the two most frequent biomarkers that were serially sampled. For S100B in severe TBI, a majority of studies indicate a t½ of about 24 hours, even if very early sampling in these patients reveals rapid decreases (1-2 hours) though possibly of non-cerebral origin. In contrast, the t½ for NSE is comparably longer, ranging from 48-72 hours in severe TBI cases. The protein GFAP (n=18) appears to have t½ of about 24-48 hours in severe TBI. The protein UCH-L1 (n=9) present a t½ around 7 hours in mild TBI, and about 10 hours in severe. Frequent sampling of these proteins revealed different trajectories with persisting high serum levels, or secondary peaks, in patients with unfavorable outcome or in patients developing secondary detrimental events. Finally, NF-L (n=2) only increased in the few studies available, suggesting a serum availability >10 days. To date, automated assays are available for S100B and NSE making them faster and more practical to use. Conclusion: Serial sampling of brain specific proteins in serum reveals different temporal trajectories that should be acknowledged. Proteins with shorter serum availability, like S100B, may be superior to proteins such as NF-L in detection of secondary harmful events when monitoring patients with TBI.